Identifying patient safety problems associated with information technology in general practice: an analysis of incident reports. Issue 11 (5th November 2015) - Magrabi, Farah; Liaw, Siaw Teng; Arachi, Diana; Runciman, William; Coiera, Enrico; Kidd, Michael R
Abstract : Objective: To identify the categories of problems with information technology (IT), which affect patient safety in general practice. Design: General practitioners (GPs) reported incidents online or by telephone between May 2012 and November 2013. Incidents were reviewed against an existing classification for problems associated with IT and the clinical process impacted. Participants and setting: 87 GPs across Australia. Main outcome measure: Types of problems, consequences and clinical processes. Results: GPs reported 90 incidents involving IT which had an observable impact on the delivery of care, including actual patient harm as well as near miss events. Practice systems and medications were the most affected clinical processes. Problems with IT disrupted clinical workflow, wasted time and caused frustration. Issues with user interfaces, routine updates to software packages and drug databases, and the migration of records from one package to another generated clinical errors that were unique to IT; some could affect many patients at once. Human factors issues gave rise to some errors that have always existed with paper records but are more likely to occur and cause harm with IT. Such errors were linked to slips in concentration, multitasking, distractions and interruptions. Problems with patient identification and hybrid records generated errors that were in principle no different to paper records. Conclusions: Problems associated with IT include perennial risks with paper records, but additional disruptions in workflow and hazards for patients unique to IT, occasionally affecting multiple patients. Surveillance for such hazards may have general utility, but particularly in the context of migrating historical records to new systems and software updates to existing systems.